2021
DOI: 10.1111/mec.15854
|View full text |Cite
|
Sign up to set email alerts
|

Founder effects shape linkage disequilibrium and genomic diversity of a partially clonal invader

Abstract: Biological invasions can wreak havoc on native communities by homogenizing environments thereby compromising ecosystem function (Pimentel et al., 2005). As globalization continues to escalate, the frequency of potential and successful biological invasions continues to increase (Seebens et al., 2017). Efforts to understand why certain species become invasive where others fail has been focused on identifying key phenotypic traits shared among invaders, such as high growth rate, high reproductive output, broad ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 145 publications
(184 reference statements)
2
39
0
Order By: Relevance
“…2017a, Flanagan et al. 2021). One exception occurs in the invaded region of the Salish Sea in Washington state and British Columbia which was sourced by a mixture of northern and southern Japanese populations.…”
Section: The Invasion History Of Agarophyton Vermiculophyllummentioning
confidence: 99%
See 2 more Smart Citations
“…2017a, Flanagan et al. 2021). One exception occurs in the invaded region of the Salish Sea in Washington state and British Columbia which was sourced by a mixture of northern and southern Japanese populations.…”
Section: The Invasion History Of Agarophyton Vermiculophyllummentioning
confidence: 99%
“…(2016, 2017a) and approximately 62,000 SNPs in Flanagan et al. (2021) found comparable levels of nuclear genetic diversity between native and non‐native regions, suggesting highly genetically diverse inocula, a highly diverse source population, multiple invasions, or some mix of the three processes. Multiple analyses definitively identified the Miyagi Prefecture (e.g., sites Soukanzan and Mangoku‐ura) as the main source of most of the Northern Hemisphere invasion (Figs.…”
Section: The Invasion History Of Agarophyton Vermiculophyllummentioning
confidence: 99%
See 1 more Smart Citation
“…Despite such bottlenecks, loss of diversity measured by molecular markers does not necessarily reflect loss of quantitative trait variation (Dlugosch and Parker, 2008b;Estoup et al, 2016). A series of studies revealed that rapid phenotypic evolution facilitated the invasion of the widespread red macroalga Agarophyton vermiculophyllum despite the fact that the species experienced a severe genetic bottleneck and increased through clonal spreading (Krueger-Hadfield et al, 2016;Sotka et al, 2018;Flanagan et al, 2021). The European starling (Sturnus vulgaris) in North America was founded by only ∼180 individuals, but local populations seem to have evolved rapidly and now show the signature of only a moderate population bottleneck (Hofmeister et al, 2021).…”
Section: Discoveries and Limitations Of Genomic Studies Of Diverse Invasive Speciesmentioning
confidence: 99%
“…[9]). Genetic bottlenecks can also contribute to performance by purging deleterious alleles, revealing beneficial cryptic variation or creating new beneficial interactions among genomic elements [3,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%